Chaperoning a7 neuronal nicotinic acetylcholine receptors - Valles, Ana Sofia (2012)
The α7 subtype of nicotinic acetylcholine receptors (AChRs) is one of the most abundant members of the Cysloop family of receptors present in the central nervous system. It participates in various physiological processes and has received much attention as a potential therapeutic target for a variety of pathologies. The importance of understanding the mechanisms controlling AChR assembly and cell-surface delivery lies in the fact that these two processes are key to determining the functional pool of receptors actively engaged in synaptic transmission. Here we review recent studies showing that RIC-3, a protein originally identified in the worm Caenorhabditis elegans, modulates the expression of α7 AChRs in a subtype-specific manner. Potentiation of AChR expression by post-transcriptional events is also critically assessed.